A New Kind of National Park for Canada:: Waterloo’s Mennonite Country Could be a Model for Managing Change in Valuable Landscapes - Shipley, Robert; Kovacs, Jason; Fitzpatrick, Anne (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract National and Provincial Parks have been a Canadian strength for a century. The approach has focused on public owned wilderness or natural lands. However, public ownership is not the only model. There is a need in populated areas of Canada to preserve valued landscapes, but neither the theory nor the practice is well developed. This paper clarifies the need, considers current efforts, outlines candidate approaches, applies a model to the Mennonite countryside of Waterloo and makes recommendations.